Decrease in skin collagen glycation with improved glycemic control in patients with insulin-dependent diabetes mellitus. - Lyons, T J (1991)
Glycation, oxidation, and nonenzymatic browning of protein have all been implicated in the development of diabetic complications. The initial product of glycation of protein, fructoselysine (FL), undergoes further reactions, yielding a complex mixture of browning products, including the fluorescent lysine-arginine cross-link, pentosidine. Alternatively, FL may be cleaved oxidatively to form N(epsilon)-(carboxymethyl)lysine (CML), while glycated hydroxylysine, an amino-acid unique to collagen, may yield N(epsilon)-(carboxymethyl)hydroxylysine (CMhL). We have measured FL, pentosidine, fluorescence (excitation = 328 nm, emission = 378 nm), CML, and CMhL in insoluble skin collagen from 14 insulin-dependent diabetic patients before and after a 4-mo period of intensive therapy to improve glycemic control. Mean home blood glucose fell from 8.7 +/- 2.5 (mean +/- 1 SD) to 6.8 +/- 1.4 mM (P less than 0.005), and mean glycated hemoglobin (HbA1) from 11.6 +/- 2.3% to 8.3 +/- 1.1% (P less than 0.001). These changes were accompanied by a significant decrease in glycation of skin collagen, from 13.2 +/- 4.3 to 10.6 +/- 2.3 mmol FL/mol lysine (P less than 0.002). However, levels of browning and oxidation products (pentosidine, CML, and CMhL) and fluorescence were unchanged. These results show that the glycation of long-lived proteins can be decreased by improved glycemic control, but suggest that once cumulative damage to collagen by browning and oxidation reactions has occurred, it may not be readily reversed. Thus, in diabetic patients, institution and maintenance of good glycemic control at any time could potentially limit the extent of subsequent long-term damage to proteins by glycation and oxidation reactions.